Review of field studies of aircraft noise-induced sleep disturbance - Michaud, David S.; Fidell, Sanford; Pearsons, Karl; Campbell, Kenneth C.; Keith, Stephen E. (The Journal of the Acoustical Society of America, 2007)
Aircraft noise-induced sleep disturbance (AN-ISD) is potentially among the more serious effects of aircraft noise on people. This literature review of recent field studies of AN-ISD finds that reliable generalization of findings to population-level effects is complicated by individual differences among subjects, methodological and analytic differences among studies, and predictive relationships that account for only a small fraction of the variance in the relationship between noise exposure and sleep disturbance. It is nonetheless apparent in the studied circumstances of residential exposure that sleep disturbance effects of nighttime aircraft noise intrusions are not dramatic on a per-event basis, and that linkages between outdoor aircraft noise exposure and sleep disturbance are tenuous. It is also apparent that AN-ISD occurs more often during later than earlier parts of the night; that indoor sound levels are more closely associated with sleep disturbance than outdoor measures; and that spontaneous awakenings, or awakenings attributable to nonaircraft indoor noises, occur more often than awakenings attributed to aircraft noise. Predictions of sleep disturbance due to aircraft noise should not be based on over-simplifications of the findings of the reviewed studies, and these reports should be treated with caution in developing regulatory policy for aircraft noise.